A área central dos aglomerados urbanos do Noroeste de Portugal - Fernandes, José Alberto Rio (2013)
The urban centre constitutes the focal point of the social, cultural and economic life of a town or region. It reflects, to a large degree, the evolution of towns: of the different urban áreas, it is the one in which changes are constant and more significant. This article analyses the expression and importance of the centres of Oporto, Braga, Guimarães, Viana do Castelo, Póvoa de Varzim and Barcelos and also discusses the distribution of different activities in those centres.